Biologically active flavonoids from Dodonaea viscosa and their structure-activity relationships - Muhammad, A.; Tel-Cayan, G.; Ozturk, M.; Nadeem, S.; Duru, M.E.; Anis, I.; Ng, S.W.; Shah, M.R. (Elsevier, 2015)
Antioxidant and anticholinesterase activities of twelve flavonoids i.e. santin (1), penduletin (2), viscosine (3), 6,7-dimethylkaempferol (4), kaempferol-3- methylether (5), 3,4'-dimethoxy-5,7-dihydroxyflavone (6), 5,7,4'-trihydroxy-3-(3-hydroxymethylbutyl)-3,6-dimethoxyflavone (7), 5,7-dihydroxy-3'-(2-hydroxy-3-methyl-3-butenyl)-3,6,4'-trimethoxy-flavon e (8), 5,7-dihydroxy-3'-(3-hydroxy-methylbutyl)-3,6,4'-trimethoxyflavone (9), 5,7-dihydroxy-3'-(4 `'-acetoxy-3''-methylbuty1)-3,6,4'-trimethoxy flavone (10), aromadendrin, (2S,3S) 3,4',5,7-tetrahydroxyflavanone (11), and pinocembrin (12), together with monohydrated crystal (1A) of 1 and anhydrous crystal (3A) of 3 - isolated from Dodonaea viscosa - were studied. The results are given as 50% inhibition concentrations (IC50). Their structure-activity relationships are discussed for both activities. Flavonoids 3 and 10 showed higher antioxidant activity in all tests. 3 Also showed moderate acetylcholinesterase (IC50: 182.97 +/- 1.25 mu M) and significant butyrylcholinesterase (IC50: 47.07 +/- 0.54 mu M) inhibitory activities. Compounds 2 (IC50: 55.78 +/- 1.01 mu M) and 3A (IC50: 58.72 +/- 1.02 mu M) were also moderate anticholinesterase agents against butyrylcholinesterase enzyme. Monohydrate crystal (1A) showed better antioxidant and anticholinesterase activities than its amorphous form (1). In contrast, the amorphous 3 exhibited better activity than the anhydrous crystal (3A). In hydrous crystal, the water molecule might be responsible for better activity. These natural flavonoids can be used as pharmaceuticals and/or preservatives in respective industries. (C) 2015 Elsevier B.V. All rights reserved.